2020
DOI: 10.3847/1538-4357/abc2cd
|View full text |Cite
|
Sign up to set email alerts
|

GRB 160625B: Evidence for a Gaussian-shaped Jet

Abstract: We present multiwavelength modeling of the afterglow from the long γ-ray burst GRB 160625B using Markov Chain Monte Carlo (MCMC) techniques of the afterglowpy Python package. GRB 160625B is an extremely bright burst with a rich set of observations spanning from radio to γ-ray frequencies. These observations range from ∼0.1 days to >1000 days, thus making this event extremely well-suited to such modeling. In this work we compare top-hat and Gaussian jet structure types in order to find best fit values for the G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 92 publications
3
11
1
Order By: Relevance
“…10 3 -. This efficiency is much lower than the typical estimates for other GRBs in the literature (Fan & Piran 2006;Zhang et al 2007;Wygoda et al 2016;Beniamini et al 2016), even though we note that a recently published study (Cunningham et al 2020) of GRB 160625B also found a low efficiency when leaving the χ e parameter free to vary. The prompt emission efficiency we find is compatible with that expected in the case of internal shocks within the jet (Rees & Meszaros 1994) with a moderate Lorentz factor contrast (Kumar 1999).…”
Section: = -+contrasting
confidence: 67%
“…10 3 -. This efficiency is much lower than the typical estimates for other GRBs in the literature (Fan & Piran 2006;Zhang et al 2007;Wygoda et al 2016;Beniamini et al 2016), even though we note that a recently published study (Cunningham et al 2020) of GRB 160625B also found a low efficiency when leaving the χ e parameter free to vary. The prompt emission efficiency we find is compatible with that expected in the case of internal shocks within the jet (Rees & Meszaros 1994) with a moderate Lorentz factor contrast (Kumar 1999).…”
Section: = -+contrasting
confidence: 67%
“…Descriptions of the MCMC implementation may be found in Refs. 176,177 and the nested sampling implementation in Ref. 20 .…”
Section: Modelingmentioning
confidence: 99%
“…We perform a comparison of the models applied in this work using their WAIC scores, described in Section 3.1 (see also Troja et al 2020;Cunningham et al 2020). We note that the WAIC analysis is not applicable to individual modes within the models, and that we only compare the overall model fits presented in Table A1.…”
Section: Model Comparisonmentioning
confidence: 99%